PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2019-2022 - Dewi, Susana; Setiawan, Feri; Karsam, Karsam (Universitas La Tansa Mashiro, 2023)
Performance and profitability are closely related to financial reports because these two things are part of financial reports. Accuracy of financial reports is one of the criteria for professionalism. Even though there are regulations regarding the submission of financial reports, the phenomenon that occurs from year to year on the Indonesian Stock Exchange (BEI) is that publicly listed firms are still late in submitting audited annual financial reports. The study of the time span and delays in publishing audited financial reports is an interesting phenomenon to research. This research aims to determine the influence of firm size, profitability, and audit opinion both partially and simultaneously on audit delay. The research method uses a quantitative/statistical study approach, testing data with the SPSS 26 for Windows program. The population of this research is all energy sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample was determined using a purposive sampling technique and 25 companies or 100 research data were obtained. The research results show that partially firm size has no effect on audit delay, profitability has no effect on audit delay, audit opinion has an effect on audit delay. And simultaneously, firm size, profitability and audit opinion influence audit delay.